1994
DOI: 10.1007/bf00019602
|View full text |Cite
|
Sign up to set email alerts
|

The stress intensity factor Green's function for a crack interacting with a circular inclusion

Abstract: The Green's function is constructed for the stress intensity factor due to the unit dipole force applied to the crack surface in the presence of a circular inclusion in front of the crack tip. An explicit functional form of the Green's function is proposed in terms of dipole force location, Young's modulus ratio and the inclusion size and position with respect to the crack tip. This is achieved through a combination of the dimensional analysis and parametric studies by means of the finite element method. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The use of Green's functions is discussed by several investigators, e.g. Synder and Cruse (1975), Rudolphi (1985), Cruse and Raveendra (1988), Li and Chudnovsky (1994), Melnikov (1995), Chen and Hasebe (1997), etc.…”
Section: Unique Integral Formulations To Overcome Bie Degeneracymentioning
confidence: 99%
“…The use of Green's functions is discussed by several investigators, e.g. Synder and Cruse (1975), Rudolphi (1985), Cruse and Raveendra (1988), Li and Chudnovsky (1994), Melnikov (1995), Chen and Hasebe (1997), etc.…”
Section: Unique Integral Formulations To Overcome Bie Degeneracymentioning
confidence: 99%
“…It was observed that for relatively flat elliptical inclusions and radially oriented crack with respect to the inclusion, as the crack orients itself towards the flat side of the inclusion the crack tip stress intensity decreases drastically. Li and Chudnovsky [8,9] performed energy analysis and examined effects of an elastic inclusion on energy release rate (ERR) for crack extension. They studied variations due to inclusion translation, rotation and expansion with respect to the crack tip and showed that a crack approaching a soft inclusion accelerated while a crack approaching a stiff inclusion slowed down.…”
Section: Introductionmentioning
confidence: 99%
“…A Green's function for a crack interacting with an inclusion has also been developed by Li and Chudnovsky (1994). A summary of these and other BIE fracture mechanics advances is given in Cruse (1996).…”
Section: Introductionmentioning
confidence: 99%